Elaboração de fórmulas farmacêuticas de uso tópico utilzando óleo essencial extraído do capim cidreira - Jesus, Josiane Gomes de (2019)
Essential oils are a mixture of compounds, which can be extracted from aromatic plants by steam distillation and are important in the perfumery, cosmetics, food and pharmaceutical industries. The aim of the study was to develop a topical cream-based formulation containing lemongrass essential oil to verify its cosmetic function and possible bactericidal function. A brief bibliographical survey of the plant, essential oils, was carried out, describing some of its characteristics and applications and the importance of legislation for topical formulation processes. The microorganisms Escherichia coli, Sthaphylococcus aureus were used in the study to verify bactericidal action of the oil, both in nature and in formulation. However, there was no evidence of action on them, because the oil did not show bactericidal capacity at the concentrations studied 2, 5, 7, 9 and 11%. Finally, the cream-based formulation developed did not change the thermal stability study performed.